UNDERSTANDING MIGRATION PATTERNS OF ANIMALS AND SOCIO-ECOLOGICAL TRANSITIONS IN GARHWAL REGION (UTTARAKHAND) DUE TO CLIMATE CHANGE - Kumar, Sandeep (International Journal of Research -GRANTHAALAYAH, 2025)
The Garhwal region of Uttarakhand, situated in the central Himalayas, stands as one of India’s most ecologically diverse and environmentally sensitive zones. Encompassing a vast altitudinal range, from subtropical valleys to alpine meadows and glaciated peaks, it harbors a unique assemblage of flora and fauna that have evolved intricate adaptations to the region’s climatic variability. The lives of both wild and domesticated animals in this mountainous landscape are deeply intertwined with seasonal rhythms, resource availability, and altitudinal migration patterns that have persisted for centuries. These migratory cycles, whether of pastoral herds moving to the “bugyals” or of wildlife following the gradient of vegetation and temperature, constitute the ecological backbone of Garhwal’s mountain systems. Here, we shall delve into the intricacies and understandings of changing/transitioning migratory patterns of animals in the concerned region, driven mainly by climate change. We shall also (briefly) allude towards the impacts laid upon socio-economic and cultural variables, in an effort to understand the parallel connections between climate change, anthropocentric dynamics and animal/livestock patterns.